Systems analysis and design people, processes and projects - Siau, Keng.; Chiang, Roger H. L.; Hardgrave, Bill C.; Gale Group (Armonk, N.Y. M.E. Sharpe, 2011)
Focuses on the personal and socio-technical aspects of systems analysis and design. Chapters are grouped into three categories: people and social systems, socio technical processes, and project teams.
pt. 1. Social systems focus : people -- pt. 2. Sociotechnical systems focus : processes -- pt. 3. Technical systems focus : projects.
Electronic reproduction.
Keywords: System analysis; System design; Electronic books